BONE MORPHOGENETIC PROTEIN-2 AND COLLAGEN TYPE 1 FROM DIFFERENT SOURCES OF DEMINERALIZED DENTINE MATRIX: RELEASE KINETIC AND CHEMOTAXIS POTENTIAL FOR OSTEOPROGENITOR CELLS - BAO, JIBO; H. E., JUN; L. I., ZILIANG; YANG, RONGQIANG; ZOU, JINYANG; DING, YIXIN; NIU, TAO; XIE, ZHIGANG; SERIWATANACHAI, DUTMANEE (International Journal of Applied Pharmaceutics, 2019)
Objective: To investigate the release of bone morphogenetic protein-2 (BMP-2) and collagen type I proteins (COL1) from different sources of demineralized dentine matrix (DDM) and their chemotaxis to mouse osteoprogenitor cells. Methods: The release kinetic of BMP-2 and COL1 was measured from custom-made DDM (CMDDM) and commercially available DDM (CADDM). Using Urist physicochemical method, CMDDM was collected from the extracted teeth in a certified dental clinic. Levels of BMP-2 and COL1 released were measured at days 1, 2, 3, 5, 7, 9, 11, and 13. Next, mouse osteoprogenitor cells, MC3T3-E1, were cultured with a variety of materials as follows: CMDDM, CADDM, Bio-Oss®, and blank control in transwell system. The number of cell migration was determined by crystal violet staining to explore chemotaxis of different DDMs to mouse osteoprogenitor cells. Results: BMP-2 was detected at 588.32 ± 14.53 pg/ml from 5 g of CMDDM. In the release kinetic assay, the concentration of BMP-2 in the CMDDM group increased rapidly and peaked at 113.9 pg/ml on day 5, almost four times higher than that of CADDM. The release of COL1 showed similar pattern in both CMDDM and CADDM; however, the amount was significantly higher in the CMDDM group. In cell culture experiment, the number of migrated MC3T3-E1 was ranked as the highest in CMDDM, followed by CADDM and Bio-Oss® (p<0.05). Conclusion: CMDDM released BMP-2 and COL1 greater than CADDM, which can induce more osteoblast-like cell migration. These results demonstrated a release kinetic of proteins and osteoinductivity of CMDDM, which supports a benefit of using autogenous bone graft.